Severe neonatal long QT syndrome type 3 treated with genotype-directed therapy and early left cardiac sympathetic denervation: a case report - Andrea Greco; Estefania Martinez-Barrios; Agustin Lujan; Oscar Campuzano Larrea; Georgia Sarquella-Brugada (European Heart Journal - Case Reports, 2026)
Abstract Background Long QT syndrome type 3 may present in fetal or neonatal life with QT prolongation, functional 2:1 atrioventricular block, and life-threatening ventricular arrhythmias. Early recognition and individualized genotype-directed management may be lifesaving. Case summary A neonate delivered after fetal bradycardia and intermittent 2:1 atrioventricular block presented with severe QT prolongation and recurrent torsades de pointes. The functional 2:1 atrioventricular block persisted despite beta blockade and magnesium administration. Because of recurrent ventricular arrhythmias, video-assisted thoracoscopic left cardiac sympathetic denervation and implantable loop recorder insertion were performed on day 8 of life. Genetic testing identified a de novo pathogenic SCN5A_p.(Ala1656Val) missense variant. Subsequent lidocaine testing demonstrated marked QT shortening, supporting sodium-channel-mediated disease and guiding treatment with mexiletine and flecainide. Long-term follow-up required implantable cardioverter-defibrillator therapy, but arrhythmic burden progressively improved. Discussion This case support the potential role of early multimodal treatment in malignant neonatal long QT syndrome type 3, combining left cardiac sympathetic denervation, continuous rhythm monitoring, and genotype-directed sodium-channel blockade.